Molecular Mechanisms of White Spot Syndrome Virus Infection and Perspectives on Treatments - Bas Verbruggen; Lisa K. Bickley; Ronny van Aerle; Kelly S. Bateman; Grant D. Stentiford; Eduarda M. Santos; Charles R. Tyler (Viruses, 2016)
Since its emergence in the 1990s, White Spot Disease (WSD) has had major economic and societal impact in the crustacean aquaculture sector. Over the years shrimp farming alone has experienced billion dollar losses through WSD. The disease is caused by the White Spot Syndrome Virus (WSSV), a large dsDNA virus and the only member of the Nimaviridae family. Susceptibility to WSSV in a wide range of crustacean hosts makes it a major risk factor in the translocation of live animals and in commodity products. Currently there are no effective treatments for this disease. Understanding the molecular basis of disease processes has contributed significantly to the treatment of many human and animal pathogens, and with a similar aim considerable efforts have been directed towards understanding host–pathogen molecular interactions for WSD. Work on the molecular mechanisms of pathogenesis in aquatic crustaceans has been restricted by a lack of sequenced and annotated genomes for host species. Nevertheless, some of the key host–pathogen interactions have been established: between viral envelope proteins and host cell receptors at initiation of infection, involvement of various immune system pathways in response to WSSV, and the roles of various host and virus miRNAs in mitigation or progression of disease. Despite these advances, many fundamental knowledge gaps remain; for example, the roles of the majority of WSSV proteins are still unknown. In this review we assess current knowledge of how WSSV infects and replicates in its host, and critique strategies for WSD treatment.